American Cosmic: UFOs, Religion, Technology, by D.W. Pasulka. (5th August 2021) - Rapport, Jeremy
Abstract : American Cosmic: UFOs, Religion, Technology, by D.W. Pasulka. 2019, Oxford University Press. Hb. $24.95. ISBN-13: 9780190692889.